2011
DOI: 10.1128/mbio.00157-11
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics of Vibrio cholerae from Nepal in 2010: Evidence on the Origin of the Haitian Outbreak

Abstract: Cholera continues to be an important cause of human infections, and outbreaks are often observed after natural disasters, such as the one following the 2010 earthquake in Haiti. Once the cholera outbreak was confirmed, rumors spread that the disease was brought to Haiti by a battalion of Nepalese soldiers serving as United Nations peacekeepers. This possible connection has never been confirmed. We used whole-genome sequence typing (WGST), pulsed-field gel electrophoresis (PFGE), and antimicrobial susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
233
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(267 citation statements)
references
References 19 publications
24
233
0
4
Order By: Relevance
“…Although the molecular and genomic data in the previous reports cited here have been interpreted as being consistent with V. cholerae being introduced to Haiti by outside visitors (5,7,8), a definitive statement of source attribution cannot yet be made. To assess source attribution, a qualified reference database (including recent strains from Nepal, India, and Cameroon, and related V. cholerae strains from concurrent epidemics) representative of global phylogenetic diversity as well as well-documented population diversity within the heterogeneous clade and its near neighbor comparators, is critical.…”
mentioning
confidence: 77%
“…Although the molecular and genomic data in the previous reports cited here have been interpreted as being consistent with V. cholerae being introduced to Haiti by outside visitors (5,7,8), a definitive statement of source attribution cannot yet be made. To assess source attribution, a qualified reference database (including recent strains from Nepal, India, and Cameroon, and related V. cholerae strains from concurrent epidemics) representative of global phylogenetic diversity as well as well-documented population diversity within the heterogeneous clade and its near neighbor comparators, is critical.…”
mentioning
confidence: 77%
“…Recent studies revealed the V. cholerae O1 ET associated with cholera outbreaks in Haiti to be genetically closely related to ET strains associated with cholera in Asia (Hendriksen et al, 2011). Based on single nucleotide polymorphism (SNP) analysis of the V. cholerae genome, the seventh cholera pandemic was shown to be transmitting worldwide via three major overlapping waves from the Ganges Delta of the Bay of Bengal, the historical home of Asiatic cholera (Mutreja et al, 2011).…”
mentioning
confidence: 99%
“…Comparative genomic analysis of closely related isolates from epidemics occupying different niches or associated with different disease manifestations is a powerful means for identifying genetic events that may have contributed to clone emergence and pathogenesis (23,(25)(26)(27). PVL has been a marker for community-associated clones of S. aureus associated with skin and soft tissue infections or severe necrotizing pneumonia (28), although increased identification of PVL + strains associated with nosocomial infections weakens this correlation (29,30).…”
Section: Resultsmentioning
confidence: 99%